2014
DOI: 10.1179/1751584x14y.0000000073
|View full text |Cite
|
Sign up to set email alerts
|

Dry sliding wear behaviour of TiC/Fe composites fabricated by exothermic dispersion of Fe–Ti–C powders

Abstract: The dry sliding wear behaviour of TiC/Fe composites was investigated. The wear surfaces of the composites were characterised by scanning electron microscopy equipped with an energy dispersive X-ray spectroscope. It was found that the mass losses of the composites increased with the increase in the applied load, but decreased slightly with the increase in the sliding velocity. The friction coefficient of the composites increased with the rising of the applied load. However, its fluctuation over the sliding dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…From the point of view of the wear properties, the microstructure of the synthesized TRLs should contain a martensitic matrix with homogeneously-dispersed TiC precipitates [ 24 , 26 ]. Moreover, published data on the wear performance of Fe-based MMCs reinforced with TiC phase suggest a significant increase in the wear resistance of TRLs with increasing the TiC fraction [ 24 , 26 , 27 , 28 , 29 ]. However, reported works have shown that during the in situ synthesis of TRLs on cast iron substrates via LA, it is difficult to maintain a homogeneous dispersion of the reinforcing phase upon increasing the Ti concentration in the melt [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the point of view of the wear properties, the microstructure of the synthesized TRLs should contain a martensitic matrix with homogeneously-dispersed TiC precipitates [ 24 , 26 ]. Moreover, published data on the wear performance of Fe-based MMCs reinforced with TiC phase suggest a significant increase in the wear resistance of TRLs with increasing the TiC fraction [ 24 , 26 , 27 , 28 , 29 ]. However, reported works have shown that during the in situ synthesis of TRLs on cast iron substrates via LA, it is difficult to maintain a homogeneous dispersion of the reinforcing phase upon increasing the Ti concentration in the melt [ 23 ].…”
Section: Introductionmentioning
confidence: 99%